On nine species of the genus Bowie (Araneae: Ctenidae) from China and Malaysia - Shang, Jun-Xuan; Tian, Yuan; Zhang, Zhi-Sheng; Wang, Lu-Yu; Yang, Zi-Zhong (Zootaxa, 2026)
Nine species of the genus Bowie Jäger, 2022 are recorded from China and Malaysia, including seven new species described here. Five species are reported from Yunnan, China: Bowie achang Shang, Zhang & Wang, sp. nov. (male, female), B. dai Shang, Zhang & Wang, sp. nov. (male, female), B. lahu Shang, Zhang & Wang, sp. nov. (male), B. nangunhe Yang, Zhang & Wang, sp. nov. (male, female) and B. wa Yang, Zhang & Wang, sp. nov. (male, female). Additionally, B. tujia Shang, Zhang & Wang, sp. nov. (male) is described from Guizhou, China, and B. weiweii Shang, Zhang & Wang, sp. nov. (male, female) from Sabah, Malaysia. The previously unknown sexes of B. lishuqiang Jäger, 2012 (male, from Chongqing, Sichuan and Guangxi of China) and B. mengla Yao & Li, 2022 (female, from Yunnan of China) are described here for the first time. Photos of habitus, copulatory organs and a distribution map for all species are provided.